Neonatal neuroblastoma in a tertiary health facility in Southwest Nigeria: a case report - Fasoranti, Ifedayo O.; Kareem, Abiodun J.; Bewaji, Temitayo O.; Samuel, Ibitoye B.; Oluwatuyi, Korede O.; Okunade, Abiola; Akinsuwa, Idowu R.; Kareem, Adesola O.; Babalola, Babatunde D.; Taiwo, Timilehin L.; Ganiyu, Adebola B.; Eniowo, Akinbowale R. (International Journal of Research in Medical Sciences, 2025)
Neuroblastoma is a pediatric neoplasm diagnosed in infancy and occurs mainly in the abdomen. There is a paucity of data in developing countries, including Nigeria. Therefore, this study aimed to report the first case of neonatal neuroblastoma in a Federal Medical Centre, Owo, Ondo state, Nigeria. We described a 4-hour-old term female neonate with multiple subcutaneous nodules and a right-sided intra-abdominal mass that crosses the midline. Examination reviewed an ill-looking neonate with multiple, painless anterior abdominal wall subcutaneous nodules and abdominal distension with a palpable right-sided abdominal mass. The abdominal MRI revealed a right abdominal mass separated from the normal-shaped kidney and an enlarged liver with multiple nodules. The liver enzymes and urinary vanillylmandelic acid were elevated. Neonatal neuroblastoma, though rarely reported among Nigerian neonates, should be considered in the differential diagnosis of abdominal mass, and the awareness should be increased among sonographers for early detection.